Social responsibility model applied to cultural management, organizational and strategic in public-private (2013)
An approach to the concept of social responsibility and the impact that is made to communities; revised from the public and private sectors, their advantages and disadvantages, scope, sectors benefiting. The rules governing the principle of social responsibility is noted. Examples of the contribution of the public and private sectors within the philosophy of each organization with the Social Responsibility and the synergy that is created with the different sectors of the economy are presented.